The role of career planning in the perception of success for faculty of sports sciences students - İsa Çiftçi; Veli Ozan Çakır (Ozlem Book Center, 2023)
The aim of the study is to understand and explain to what extent and how individual career planning affects an individual's perception of personal success. The sample group consists of a total of 682 students, 304 female and 378 males, studying at the Faculty of Sports Sciences of Bingol University and Fırat University. In the research, the "Career Planning Scale" and "Personal Achievement Perception Scale" were used to collect personal information and data. In the analysis of the data, the level of the relationship between the independent and dependent variables was determined using the Pearson correlation test, and the effect of the independent variable on the dependent variable was determined using the linear regression test. The effects of career planning sub-dimensions, self-evaluation, defining opportunities, setting goals, and creating a plan on the personal success of the students participating in the research were found to be statistically significant (p<0.05). As a result, self-evaluation, identifying opportunities, setting goals, and creating plans, which are among the sub-dimensions of career planning, significantly affect personal success. Therefore, developing and directing these career planning processes in a positive way can significantly increase individuals' perceptions of personal success.